Efficient removal of antibiotics by a novel magnetic adsorbent: Magnetic activated carbon/chitosan (MACC) nanocomposite - KERKEZ KUYUMCU, ÖZGE (ELSEVIER SCIENCE BV, 2017)
A novel adsorbent, Fe3O4/activated carbon/chitosan (MACC: Magnetic activated carbon/chitosan) was prepared by a simple coprecipitation method. MACC was characterized by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), scanning electron microscopy (SEM), vibrating sample magnetometry (VSM), and surface area analysis. MACC adsorption ability was tested for three commonly used hazardous antibiotics: ciprofloxacin, erythromycin, and amoxicillin. Langmuir isotherm model and pseudo second order kinetic model were best fitted with experimental results. Superior uptake values were found with using MACC; 90.10, 178.57 and 52631 mg/g were calculated as the theoretical adsorption capacity (g,n) using Langmuir isotherm for ciprofloxacin, erythromycin, and amoxicillin, respectively. Finally, MACC is considered as a promising magnetically separable efficient adsorbent for antibiotics removal. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Fe3O4; Activated carbon; Chitosan; Antibiotic adsorption; WALLED CARBON NANOTUBES; AQUEOUS-SOLUTION; DRUG-DELIVERY; SULFONAMIDE ANTIBIOTICS; AMOXICILLIN REMOVAL; ADSORPTIVE REMOVAL; WASTE-WATER; CHITOSAN; CIPROFLOXACIN; COMPOSITE